Impact of Elevated CO2 and Reducing the Source-Sink Ratio by Partial Defoliation on Rice Grain Quality – A 3-Year Free-Air CO2 Enrichment Study - Gao, Bo; Hu, Shaowu; Jing, Liquan; Wang, Yunxia; Zhu, Jianguo; Wang, Kai; Li, Hongyang; Sun, Xingxing; Wang, Yulong; Yang, Lianxin (Frontiers in Plant Science, 2021)
Evaluating the impact of increasing CO2 on rice quality is becoming a global concern. However, whether adjusting the source-sink ratio will affect the response of rice grain quality to elevated CO2 concentrations remains unknown. In 2016-2018, we conducted a free-air CO2 enrichment experiment using a popular japonica cultivar grown at ambient and elevated CO2 levels (eCO2, increased by 200 ppm), reducing the source-sink ratio via cutting leaves (LC) at the heading stage, to investigate the effects of eCO2 and LC and their interactions on rice processing, appearance, nutrition, and eating quality. Averaged across 3 years, eCO2 significantly decreased brown rice percentage (-0.5%), milled rice percentage (-2.1%), and head rice percentage (-4.2%) but increased chalky grain percentage (+22.3%) and chalkiness degree (+26.3%). Markedly, eCO2 increased peak viscosity (+2.9%) and minimum viscosity (+3.8%) but decreased setback (-96.1%) of powder rice and increased the appearance (+4.5%), stickiness (+3.5%) and balance degree (+4.8%) of cooked rice, while decreasing the hardness (-6.7%), resulting in better palatability (+4.0%). Further, eCO2 significantly decreased the concentrations of protein, Ca, S, and Cu by 5.3%, 4.7%, 2.2%, and 9.6%, respectively, but increased K content by 3.9%. Responses of nutritional quality in different grain positions (brown and milled rice) to eCO2 showed the same trend. Compared with control treatment, LC significantly increased chalky grain percentage, chalkiness degree, protein content, mineral element levels (except for B and Mn), and phytic acid content. Our results indicate that eCO2 reduced rice processing suitability, appearance, and nutritional quality but improved the eating quality. Rice quality varied significantly among years; however, few CO2 by year, CO2 by LC, or CO2 by grain position interactions were detected, indicating that the effects of eCO2 on rice quality varied little with the growing seasons, the decrease in the source-sink ratios or the different grain positions.